Developmental psychology and young children's religious education - Petrovich, Olivera (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Developmental Psychology and Young Children's Religious Education sets out to identify the conceptual pre-requisites for young children's religious education learning and clearly highlights the challenges that children and their teachers encounter in the RE educational process. This book is essential reading for students and researchers in developmental psychology, Religious Education, teacher education, Education Studies and cultural anthropology"--
Introduction -- Research design and fieldwork: Rationale and method -- Children's perceptions of and attitudes to school RE: Interview findings -- Everyday religious understanding: The natural-theological reasoning test -- Children's concepts of God: Everyday and RE-based -- Teachers' perceptions of young children's abilities for RE learning -- Religious understanding in the early years: What can RE learn from young children?
Keywords: Religious education -- Psychology; Children -- Religious life; Child development; EDUCATION / General; EDUCATION / Elementary; EDUCATION / Multicultural Education